2003
DOI: 10.1046/j.1365-2133.2003.05539.x
|View full text |Cite
|
Sign up to set email alerts
|

Expansion of vitiligo lesions is associated with reduced epidermal CDw60 expression and increased expression of HLA-DR in perilesional skin

Abstract: These results support an active role of melanocytes within the skin immune system, and associate their loss in generalized vitiligo with a cell-mediated immune response mediated by type 1 cytokines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
28
0
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 36 publications
5
28
0
2
Order By: Relevance
“…We found that IFN-γ inducible CDw60, representative of the ganglioside GD3, was upregulated in perilesional skin [36]. The type 1 cytokine profile observed for T cells isolated directly from depigmenting lesions likewise supports a T cell mediated autoimmune response.…”
Section: Involvement Of T Cells In Depigmentationsupporting
confidence: 57%
“…We found that IFN-γ inducible CDw60, representative of the ganglioside GD3, was upregulated in perilesional skin [36]. The type 1 cytokine profile observed for T cells isolated directly from depigmenting lesions likewise supports a T cell mediated autoimmune response.…”
Section: Involvement Of T Cells In Depigmentationsupporting
confidence: 57%
“…variety of cytokines, most notably IFN-g (Barreto et al, 2003). The latter cytokine is generated in perilesional vitiligo skin by infiltrating T cells (Le Poole et al, 2003;WankowiczKalinska et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…19-23 Moreover, the reduced expression of GD3 (which contributes to keratinocyte apoptosis) induces a compensatory mechanism of epidermal thickening to protect the affected skin from UV radiation damage. 23 Finally, two recent retrospective studies have not detected a statistically significant increase of non- melanoma skin cancer (first study) or non-melanoma and melanoma skin cancers (second study) in patients with vitiligo, compared to the general population. Moreover, this last retrospective study, did not found a trend of increasing prevalence of these skin cancers in the subgroup of patients treated with PUVA and Narrow-Band UVB, adjusted for age and time of exposure during life.…”
Section: Epidemiological Aspectsmentioning
confidence: 99%